PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Media Riset Akuntansi, 2022)
This study aims to examine the effect of activity ratio, leverage, liquidity, profitability, and firm size on firm value. The population of this study are manufacturing companies sub-sector food and beverage as well as sub-sector cigarette listed on the Indonesia Stock Exchange in the period of 2016-2020, which amounted 31 companies. Purposive sampling was used as a sampling method and obtained a sample of 90 companies. The data analysis method used was multiple linear regression using SPSS software version 25. The results showed that activity ratio, liquidity, and firm size have significant positive effect on firm value. Furthermore, leverage and profitability have insignificant effect on firm value